2019
DOI: 10.1111/bph.14817
|View full text |Cite
|
Sign up to set email alerts
|

Local controlled release of corticosteroids extends surgically induced joint instability by inhibiting tissue healing

Abstract: Background and PurposeCorticosteroids are intra‐articularly injected to relieve pain in joints with osteoarthritis (OA) or acute tissue damage such as ligament or tendon tears, despite its unverified contraindication in unstable joints. Biomaterial‐based sustained delivery may prolong reduction of inflammatory pain, while avoiding harmful peak drug concentrations.Experimental ApproachThe applicability of prolonged corticosteroid exposure was examined in a rat model of anterior cruciate ligament and medial meni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 80 publications
2
13
2
Order By: Relevance
“…49 Studies have shown that IA CS treatment is used in rat OA models, and there is significant relief of pain. 50,51 In our study, IA CS was applied to the second group and IA HA was applied to the third group, and according to the post-OA, run duration, mean stance, paw print length, paw print width, paw print area, stride length, and swing speed recovered significantly. In addition, amelioration was observed in the scores obtained after histological analysis compared to the post-OA scores.…”
Section: Discussionmentioning
confidence: 76%
“…49 Studies have shown that IA CS treatment is used in rat OA models, and there is significant relief of pain. 50,51 In our study, IA CS was applied to the second group and IA HA was applied to the third group, and according to the post-OA, run duration, mean stance, paw print length, paw print width, paw print area, stride length, and swing speed recovered significantly. In addition, amelioration was observed in the scores obtained after histological analysis compared to the post-OA scores.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, in human tissue, TA inhibited loss of proteoglycans in co-culture of human cartilage tissue with synovium [ 70 ], and in equine cartilage stimulated with IL-1β decreased COX-2 and matrix metalloproteinase gene expression [ 71 ]. However, prolonged intra-articular exposure of TA in joints with acute trauma must be avoided, as it has been found to exacerbate joint instability and associated joint degeneration in an experimental model [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empty nor TA-PEAMs influenced articular cartilage quality [ 12 ]. However, in a rat model of instability-induced OA, local microspheres-based release of TA was shown to aggravate disease, which was not seen in the animals treated with bolus injection nor in healthy joints injected with TA-loaded PEAMs, indicating that the prolonged exposure to TA in combination with joint trauma was the cause [ 26 ]. Moreover, TA inhibited cell outgrowth from tissue, indicating a possible effect on tissue healing [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Animals were euthanized after 6 weeks with CO 2 . For the ACLT model, OA was induced unilaterally through anterior cruciate ligament transection and partial medial meniscectomy in the left knee of 6 rats that were randomly taken from their cages, under general isoflurane anesthesia [31]. After 16 weeks, rats were euthanized with CO 2 .…”
Section: Animal Modelsmentioning
confidence: 99%